THE PROTECTION OF PECALANG AS A SECURITY AT CONFERENCES (BETWEEN FUNCTIONS IN THE CUSTOMARY VILLAGE AND AS AN EMPLOYEE) - Wiryawan, I Wayan Gde (Brawijaya Law Journal, 2014)
Pecalang is a unit of traditional security officers in Bali, who have the authority to maintain the order and security in the region of customary village. This research is normative legal research. Legal materials derived from primary legal materials, secondary legal materials, and tertiary legal materials. Pecalang as an instrument for securing the customary village is the unity of the traditional safeguards of every customary village in Bali in charge of maintaining the order in their village. The existence of the pecalang in securing the conference is a requirement of the event organizer. Pecalang as a non-permanent employee in securing the conference employed only in a specified period that is prior to and during the conference. As non-permanent employees then pecalang are entitled to protection.